(untitled) (Scientific journal of the Fergana State University, 2024)
The 21st century is the era of globalization, and by this time, digital information technologies are widely developed, and digitalization processes are also increasing rapidly. In the age of such advanced technologies, a number of software programs have been created to work with different types of tables, which are also useful for science, in the analysis of researches and questionnaires. These include Microsoft Excel, DA SYSTEM, IBM SPSS and a number of similar programs. In this article, one of the programs that help researchers in analyzing the results of sociological research, i. e. IBM SPSS program, and its functions are mentioned.